GLOBAL VISIBILITY OF ASIAN UNIVERSITIES’ OPEN ACCESS INSTITUTIONAL REPOSITORIES - A., Abrizah; A., Noorhidawati; K., Kiran (Malaysian Journal of Library and Information Science, 2010)
This paper highlights the current state of open access repositories of Asian universities. It describes their characteristics in terms of types, contents, disciplines, language, technical and operational issues, and policy. The web performance of Asian institutional repositories as reflected through global visibility and impact of the repositories in Open Directory of Open Access Repository (OpenDOAR), is also examined; as well as the performance of Asian top-ranked universities in the archiving and sharing their research output through institutional repositories, based on the Ranking Web of World Repositories (RWWR). Findings signify Japan as the biggest contributor of Asian repositories, followed by India and Taiwan. An investigation of the status of these universities revealed that out of the 191 Asian organizational institutional repositories identified in this study, only 48 are listed in the Top 400 RWWR. This implies that only 12% of Asian institutional repositories are visible and incorporate good practices in their web publication as extracted from the, quantitative webometrics indicators used by the ranking. Out of these 48 institutions, 29 are among the Asian Top 200 universities. However, only 14 of these 29 universities were ranked top 100 in the RWWR. It is revealed that some of the top ranked universities in Asia are not actively contributing to the open access movement. It is suggested that if the web performance of an institutional repository of a research institution is below the expected position, the university authorities should reconsider their web policy to increase the volume and quality of their intellectual output / research publications through institutional repositories